AI-racer: An immersive AI-enabled VR-tool for alpine ski racing - Bruhin, B.; Bünner, M.; Délèze, F.; Notari, N.; Guillaume, S.; Schwyn, S. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The choice of the racing line is a key success factor in alpine ski racing. Nevertheless, to define before the race a "proper" racing line for a given racing track remains a highly subjective process for coaches and athletes, as objective quality criteria for racing lines are not available. As such, the definition of racing lines and racing strategy is until now not accessible for scientific discussion opening up the room for myths and subjective rules-of thumb. The aim of this work is to establish a formal procedure for the computation of optimal racing lines before the race. With this, we hope to introduce objective factors supplementing the already available subjective factors.